2006
DOI: 10.1007/s00330-006-0227-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of orbital tumors

Abstract: This contribution provides an overview of diseases of eye and orbit and their appearance on magnetic resonance imaging. In recent years the diagnosis of eye and orbit pathology has profited significantly from increasingly sophisticated technical developments in the field of tomographic methods. Due to the small size of the examination area the improvement in spatial resolution and soft tissue contrast leads to an increase in image quality. In most clinical questions concerning eye and orbit pathologies magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…Coils of 8-to 12-cm diameter are called orbital coils and used to examine external eye muscles or compare structures in both orbits. 10 Combining surface coils to form so-called phased arrays has been shown to improve SNR, 19,20 but our combination of diŠerent coils was not equivalent to a phased array coil. The double loop array coil (2 medium coils arranged perpendicular to each other) decreased the SNR considerably, possibly because of coupling between the coils.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Coils of 8-to 12-cm diameter are called orbital coils and used to examine external eye muscles or compare structures in both orbits. 10 Combining surface coils to form so-called phased arrays has been shown to improve SNR, 19,20 but our combination of diŠerent coils was not equivalent to a phased array coil. The double loop array coil (2 medium coils arranged perpendicular to each other) decreased the SNR considerably, possibly because of coupling between the coils.…”
Section: Discussionmentioning
confidence: 89%
“…9 A head coil can also be used to examine orbital content and has been found useful for comparing structures in the 2 orbits. 10,11 Previous studies indicated that use of the appropriate coil is decisive in the success of orbital MR imaging. 10 Earlier results also suggest that the use of a high resolution microscopy coil dramatically improves image resolution, enabling detailed assessment of the structures of the orbit and globe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Table 2). The right orbit was involved in 36 patients with benign tumor and 11 patients with malignant tumor.…”
Section: Imaging Findingmentioning
confidence: 99%
“…Previous study observed that the CT and MR images are modalities of choice for assessment of orbital tumors [7]. It is well known that the computed tomography and magnetic resonance imaging have the most important effective on the characterization of the orbital tumors and act vital role in the management of the orbital tumor [8][9][10]. Therefore, understanding radiological features can facilitate the differentiation of benign from malignant orbital soft tissue masses.…”
Section: Introductionmentioning
confidence: 99%